(untitled) - Harrison, Brian (London, 1963)
This book brings shape to the idea that 'to understand the present and to anticipate the future, one must know enough of the past, enough to have a sense of the history of a people.' With an approachable writing style and comprehensive content, this unique text was written for business readers interested in improving their understanding of this important region.
Keywords: Đông Nam Á,Southeast Asia; Lịch sử,History